Beneficial effect of computer-based multidomain cognitive training in patients with mild cognitive impairment. Issue 6 (2nd November 2021) - Nousia, Anastasia; Martzoukou, Maria; Siokas, Vasileios; Aretouli, Eleni; Aloizou, Athina-Maria; Folia, Vasiliki; Peristeri, Eleni; Messinis, Lambros; Nasios, Grigorios; Dardiotis, Efthimios
Abstract: The purpose of the present study was to explore the effects of computer-based multidomain cognitive training program on Greek patients with Mild Cognitive Impairment (MCI). Forty-six patients with MCI were randomly divided into two groups; (a) the training group, which received a computer-based multidomain cognitive training program with the use of the RehaCom software and (b) the control group, which underwent standard-clinical care. The duration of the computer-based training program was 15 weeks, administered twice a week for approximately one hour per session. Analysis of the baseline versus endpoint performance of each group demonstrated that in the control group delayed memory and executive function had deteriorated over the observation period of 15 weeks, while improvement was observed in the training group's performance on delayed memory, word recognition, Boston Naming Test (BNT), Clock Drawing Test (CDT), Semantic Fluency (SF), Trail Making Test-A (TMT-A) and Trail Making Test-B (TMT-B). Comparison between the two groups presented asignificant effect of the intervention for most cognitive domains. These findings are promising for the development of training methods designed to delay cognitive decline in patients with MCI, which is considered to be the prodromal stage of Alzheimer's Disease (AD).